Codeswitching use of tertiary level mathematics teachers and students' class participation - Bravo, Karizza Piedad (College of Education, University of the Philippines Diliman, 2017)
This paper reports on the Tagalog-English codeswitching use of mathematics teachers in classroom discourse, and its relationship with students' participation. Six research questions were designed for this inquiry. Questions 1, 2, and 3 were aimed at identifying and describing the types, functions, and frequency of mathematics teachers' codeswitching, respectively. Meanwhile, Questions 4, 5, and 6 sought to identify the correlation between codeswitching types and class participation, functions and class participation, and frequency and class participation, respectively. A mixed method approach was used to gather data from four math teachers through a series of class observations. Interview sessions with the four teachers and eight selected students were done to validate the results of class observations. The results of the study show that in terms of codeswitching types, intersentential, intrasentential, and tag switching were all present in math teachers' spoken discourse. . Of the three codeswitching types, intrasentential codeswitching was used quite extensively in math teachers' utterances, while tag switching was used sparingly. As for the functions of codeswitching, the results show that ideation, textual, and interpersonal were used: the ideation function was used to complement math instruction and to support other math-related tasks, the interpersonal function was utilized for rapport building and socialization, and the textual function was concerned with the use of codeswitching to mark transitions and highlight different focuses. Likewise, it was noted that under each codeswitching function, subtypes emerged. With regard to the codeswitching frequency of college math teachers, the results showed that the codeswitching frequencies ranged from moderate to high. In terms of the correlation between codeswitching types, functions, and frequencies, and students' class participation, the statistical results show a significant relationship among the three pairs of variables. This means that the Tagalog-English codeswitching of math teachers is associated with students' participation in classroom discourse. In general, gathered data not only confirm the findings of previous studies on codeswitching, but also offer additional insights essential to understanding the role of math teachers' codeswitching in spurring participation of students in the tertiary level. Future research possibilities are highlighted and pedagogical implications for tertiary level multilingual classrooms are considered.